Trans-Lamina Terminalis Approach to Third Ventricle using Supraorbital Craniotomy: Technique Description and Literature Review for Outcome Comparison with Anterior, Lateral and Trans-Sphenoidal Corridors - Krishna, V.; Blaker, B.; Kosnik, L.; Patel, S.; Vandergrift, W. (min - Minimally Invasive Neurosurgery, 2011)
The trans-lamina terminalis approach has been described to remove third ventricular tumors. Various surgical corridors for this approach include anterior (via bifrontal craniotomy), anterolateral (via supra-orbital craniotomy), lateral (via pterional craniotomy) and trans-sphenoidal corridors. Supra-orbital craniotomy offers a minimally invasive access for resection of third ventricular tumors.The trans-lamina terminalis technique through a supra-orbital craniotomy is described. Also, a literature review of clinical outcome data was performed for the comparison of different surgical corridors (anterior, antero-lateral, lateral, and trans-sphenoidal).The operative steps and anatomic landmarks for supra-orbital craniotomy are discussed, along with 3 representative cases and respective outcomes. Gross total resection was achieved in 2 patients, and one patient required reoperation for recurrence. Based on the current literature, the clinical outcomes after supra-orbital craniotomy for trans-lamina terminalis approach are comparable to other surgical corridors.The supra-orbital craniotomy for trans-lamina terminalis approach is a valid surgical choice for third ventricular tumors. The major strengths of this approach include minimal brain retraction and direct end-on view; however, the long working distance is a major limitation. The clinical outcomes are comparable to other surgical corridors. Sound understanding of major strengths, limitations, and strategies for complication avoidance is necessary for its safe and effective application.
Keywords: key-hole approach; minimally invasive surgery; outcome; neurooncology